(untitled) (Journal of the College of Education for Women, 2014)
This paper presents a stylistic analysis of two poems of well-known poets of the English literature, namely; E.E. Cummings and the Irish noble laureate Seamus Heaney. The researcher’s attempt here is to approach Cummings’s poem “maggie and milly and molly and may” and Heaney’s “A Kite for Aibhín” from the stylistics’ point of view. The paper also analyzes the poems using the tools of linguistics with a view to make their meaning explicit. It is worth noting that stylistics as a scientific discipline is really beneficial to those who are teaching and studying English language and literature. No matter whether English is the native, second or the foreign language. Not only foreign students but also the speakers of the English language can benefit from stylistics. They can get linguistic beside literary competence. Nowadays, stylistics with its tools and methods of linguistics can help to a logical and scientific understanding of the literary texts based on linguistic evidence.